Lead-free composite piezoelectric ceramic material and preparation method thereof

By combining micron and nano-level piezoelectric ceramic materials at specific molar ratios, the problem of insufficient electrical performance and stability of existing lead-free piezoelectric ceramic materials is solved, and the high voltage electrical performance and room temperature body resistivity is improved, which is suitable for high-temperature conditions.

CN119241233BActive Publication Date: 2025-03-11SHANGHAI WOEION HEALTH TECH GROUP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411091264.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2025-03-11
Estimated Expiration
2044-08-09

AI Technical Summary

Technical Problem

Existing lead-free piezoelectric ceramic materials have shortcomings in electrical performance and stability, and it is difficult to meet the needs of applications such as sensors and brakes.

Method used

The composite preparation method of micron Mg (1-x) SrxZr0.2Ti0.8O3 base-layer structure piezoelectric ceramic material and nanoNa (1-y) SryCe0.15Ti0.85O3 base-layer structure piezoelectric ceramic material is used to construct excellent pinning effects by regulating the molar ratio and particle size, and improve the density and electrical properties of the ceramics.

Benefits of technology

The high-voltage electrical performance and stability of lead-free composite piezoelectric ceramic materials are achieved, the resistivity and density of room temperature are improved, and the stable performance of the material under high temperature conditions is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241233B_ABST
    Figure CN119241233B_ABST
Patent Text Reader

Abstract

The present invention discloses a lead-free composite piezoelectric ceramic material and a preparation method thereof. The lead-free composite piezoelectric ceramic material is composed of micron Mg (1‑x) Sr x Zr 0.2 Ti 0.8 O3-based piezoelectric ceramic materials and nano-Na (1‑y) Sr y Ce 0.15 Ti 0.85 O3 matrix structure piezoelectric ceramic material, by adjusting the molar ratio of micron and nano calcined powder composite composition; mixing the pre-synthesized Mg (1‑x) Sr x Zr 0.2 Ti 0.8 O3 group and Na (1‑y) Sr y Ce 0.15 Ti 0.85 The O3-based piezoelectric ceramic material is then ground, formed, sintered and polarized in sequence. The lead-free composite piezoelectric ceramic material of the present invention has high piezoelectric performance and low dielectric loss, improves the room temperature volume resistivity and density of the lead-free composite piezoelectric ceramic material, and makes the performance of the lead-free composite piezoelectric ceramic material more stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a lead-free composite piezoelectric ceramic material and a preparation method thereof, belonging to the technical field of piezoelectric ceramics. Background Art

[0002] Piezoelectric ceramics are widely used in the industrial production of various components, assemblies, and equipment, such as sensors (sensing elements) and brakes (piezoelectric actuators). Piezoelectric ceramic materials, such as lead zirconate titanate ceramic systems, have high piezoelectric constants, but contain lead. During production, manufacturing, use, and disposal, they will cause varying degrees of damage and pollution to the human body and the surrounding environment. It is urgent to develop suitable lead-free piezoelectric ceramic materials. At present, the main research directions for lead-free piezoelectric ceramic materials are: lead-free piezoelectric ceramic systems such as barium titanate-based, niobate-based, and BNT-based; the existing barium titanate-based lead-free piezoelectric ceramic materials have poor electrical properties and are difficult to effectively improve through doping; niobate-based lead-free piezoelectric ceramic materials have low density and difficult sintering processes, and their performance is affected by temperature and humidity; BNT-based lead-free piezoelectric ceramics have high coercive fields, and the density and chemical stability of ceramics are poor; therefore, a lead-free composite piezoelectric ceramic material with excellent piezoelectricity and stability is developed to be able to be used in sensors and brakes. Summary of the invention

[0003] In view of at least one problem existing in the above-mentioned prior art, the present invention provides a lead-free composite piezoelectric ceramic material and a preparation method thereof. The lead-free composite piezoelectric ceramic material has high piezoelectric performance and low dielectric loss, improves the room temperature volume resistivity and density of the lead-free composite piezoelectric ceramic material, and makes the performance of the lead-free composite piezoelectric ceramic material more stable.

[0004] In order to achieve the above object, the present invention adopts the following technical scheme: a lead-free composite piezoelectric ceramic material composed of micron Mg (1-x) Sr x Zr 0.2 Ti 0.8 O3-based piezoelectric ceramic materials and nano-Na (1-y) Sr y Ce 0.15 Ti 0.85 The O3-based piezoelectric ceramic material is composited by adjusting the molar ratio of micron and nano calcined powders, wherein x and y are the molar fractions of Sr, respectively, x is 0.72-0.8, and y is 0.6-0.66.

[0005] Preferably, in the lead-free composite piezoelectric ceramic material, Mg (1-x) Sr x Zr 0.2 Ti 0.8The particle size of O3-based piezoelectric ceramic materials is 1~2μm; Na (1-y) Sr y Ce 0.15 Ti 0.85 The particle size of O3-based piezoelectric ceramic materials is 300~650nm.

[0006] Preferably, the Mg in the lead-free composite piezoelectric ceramic material (1-x) Sr x Zr 0.2 Ti 0.8 O3-based piezoelectric ceramic materials and Na (1-y) Sr y Ce 0.15 Ti 0.85 The O3-based piezoelectric ceramic material has a molar ratio of 0.65:0.35.

[0007] The present invention also provides a method for preparing a lead-free composite piezoelectric ceramic material, which is prepared by the following steps:

[0008] (1) SrCO3, MgO, ZrO2 and TiO2 are first used as raw materials, and the mixture is mixed, pressed, pre-sintered and ground to obtain a micron sintered powder with a particle size of 1-2 μm;

[0009] (2) First, SrCO3, Na2CO3, ZrO2 and TiO2 are used as raw materials, and the mixture is mixed, pressed, pre-sintered and ground to obtain a nano-sintered powder with a particle size of 300-650 nm;

[0010] (3) drying the mixture of micron sintered powder and nano sintered powder, adding a binder to mix, and then pressing, cold isostatic pressing, and sintering to obtain piezoelectric ceramics;

[0011] (3) The piezoelectric ceramics are polarized to obtain a lead-free composite piezoelectric ceramic material.

[0012] Preferably, the preparation method of the lead-free composite piezoelectric ceramic material comprises the following specific steps:

[0013] S1. Preparation of micronized Mg (1-x) Sr x Zr 0.2 Ti 0.8 O3-based piezoelectric ceramic materials

[0014] S1.1, first use SrCO3, MgO, ZrO2 and TiO2 as raw materials, according to the chemical formula Mg (1-x) Sr x Zr 0.2 Ti 0.8O3 calculates and weighs the required raw materials, where x is the molar fraction of Sr, and x is 0.7-0.8. The raw materials are mixed using a conventional ball mill, dried, and pressed into blocks;

[0015] S1.2, then place it in a muffle furnace, heat it to 825~860℃, keep it warm for 2~3h for pre-sintering, and then use a traditional ball mill to grind it to form a powder with an average particle size of 1~2μm, and obtain micron sintered powder, i.e. micron Mg (1-x) Sr x Zr 0.2 Ti 0.8 O3 matrix structure piezoelectric ceramic material;

[0016] S2. Preparation of Nano-Na (1-y) Sr y Ce 0.15 Ti 0.85 O3-based piezoelectric ceramic materials

[0017] S2.1, first use SrCO3, Na2CO3, CeO2 and TiO2 as raw materials, according to the chemical formula Na (1-y) Sr y Ce 0.15 Ti 0.85 O3 calculates and weighs the required raw materials, where y is the molar fraction of Sr, y is 0.6-0.65, mixes the raw materials using a conventional ball mill, dries and presses them into blocks;

[0018] S2.2, then placed in a muffle furnace, heated to 825~860℃, kept warm for 2~3h for pre-sintering, and then ground using a high-energy ball mill to form a powder with an average particle size of 300~650nm to obtain a nano calcined powder, i.e., nano Na (1-y) Sr y Ce 0.15 Ti 0.85 O3 matrix structure piezoelectric ceramic material;

[0019] S3. Preparation of lead-free composite piezoelectric ceramic materials

[0020] S3.1, mixing the micron calcined powder and the nano calcined powder according to a certain molar ratio using a conventional ball mill, and drying to obtain a mixed calcined powder;

[0021] S3.2, adding a binder to the mixed calcined powder, mixing it evenly by conventional ball milling, and then pressing it into shape, and then cold isostatic pressing it to obtain a ceramic body;

[0022] S3.3, placing the ceramic body in a muffle furnace for sintering, and then cooling to room temperature in the furnace to obtain a piezoelectric ceramic;

[0023] S3.4. Polarization treatment: The piezoelectric ceramic is coated with platinum electrodes and polarized in silicone oil to obtain a lead-free composite piezoelectric ceramic material.

[0024] Preferably, in steps S1.1, S1.2, S2.1, S3.1 and S3.2, the milling medium of conventional ball milling is anhydrous ethanol; and in step S2.2, the milling medium of high-energy ball milling is anhydrous ethanol.

[0025] Preferably, in steps S1.1 and S2.1, the rotation speed of the conventional ball mill is 250-350 rpm, and the time is 16-24 h.

[0026] Preferably, in step S1.2, the rotation speed of the conventional ball mill is 250-350 rpm, and the time is 12-16 h.

[0027] Preferably, in step S2.2, the rotation speed of the high energy ball mill is 450-550 rpm, and the time is 1-3 h.

[0028] Preferably, in step S3.1, the rotation speed of the conventional ball mill is 250-350 rpm, and the time is 8-12 h.

[0029] Preferably, in step S3.2, the rotation speed of the conventional ball mill is 100-150 rpm, and the time is 6-8 h.

[0030] Preferably, the drying temperature of steps S1.1, S2.1 and S3.1 is 85-95°C.

[0031] Preferably, in step S3.2, the binder is polyvinyl alcohol, and the amount of the binder added is 0.45wt% of the mixed calcined powder.

[0032] Preferably, in step S3.2, the pressure of cold isostatic pressing is 180-200 MPa, and the pressure is maintained for 30-60 seconds.

[0033] Preferably, in step S3.3, the sintering temperature is 1000-1080° C., and the sintering time is 4-8 hours.

[0034] Preferably, in step S3.4, the polarization temperature is 140-150° C., the polarization electric field is 6-8 kV / mm, and the polarization time is 25-35 min.

[0035] Beneficial effects of the present invention:

[0036] (1) The present invention uses micron Mg (1-x) Sr x Zr 0.2 Ti 0.8 O3-based piezoelectric ceramic materials and nano-Na (1-y) Sr y Ce0.15 Ti 0.85 The O3-based piezoelectric ceramic material is composited to form a lead-free composite piezoelectric ceramic material, which has high piezoelectric properties and stable properties, and the room temperature resistivity is improved, and it still has good stability at high temperatures; and through two different material bases and constructing micron and nanometer particle sizes, an excellent pinning effect is formed, which can effectively avoid the decrease of d33 while obtaining a good mechanical quality factor Qm and electromechanical coupling coefficient Kp; the present invention utilizes micron and nanometer calcined powders to promote the sintering of ceramics and improve the density of piezoelectric ceramics; the preparation method of the present invention is simple to operate, stable in process, and easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 is the relative dielectric constant ε of the present invention r Graph of the change with temperature. DETAILED DESCRIPTION

[0038] The technical scheme in the implementation of the present invention is clearly and completely described below in conjunction with the accompanying drawings. The described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the conditions recommended by the normal conditions or the manufacturers. If the manufacturers are not specified in the reagents, instruments, and components used, they are all conventional products that can be purchased commercially.

[0039] The present invention provides a lead-free composite piezoelectric ceramic material composed of micron Mg (1-x) Sr x Zr 0.2 Ti 0.8 O3-based piezoelectric ceramic materials and nano-Na (1-y) Sr y Ce 0.15 Ti 0.85 O3-based piezoelectric ceramic material is composited by adjusting the molar ratio of micron and nano calcined powders, wherein x and y are the molar fractions of Sr, x is 0.7-0.8, y is 0.6-0.65; Mg (1-x) Sr x Zr 0.2 Ti 0.8 The particle size of O3-based piezoelectric ceramic materials is 1~2μm; Na (1-y) Sr y Ce 0.15 Ti 0.85 The particle size of O3-based piezoelectric ceramic materials is 300~650nm; Mg (1-x) Srx Zr 0.2 Ti 0.8 O3-based piezoelectric ceramic materials and Na (1-y) Sr y Ce 0.15 Ti 0.85 The O3-based piezoelectric ceramic material has a molar ratio of 0.65:0.35.

[0040] The present invention also provides a method for preparing a lead-free composite piezoelectric ceramic material, the specific steps of which are as follows:

[0041] S1. Preparation of micronized Mg (1-x) Sr x Zr 0.2 Ti 0.8 O3-based piezoelectric ceramic materials

[0042] S1.1, first use SrCO3, MgO, ZrO2 and TiO2 as raw materials, according to the chemical formula Mg (1-x) Sr x Zr 0.2 Ti 0.8 O3 calculates and weighs the required raw materials, where x is the molar fraction of Sr, and x is 0.7-0.8. The raw materials are mixed using a conventional ball mill at 250-350 rpm for 16-24 hours, and the ball milling medium is anhydrous ethanol. The raw materials are dried at 85-95°C and pressed into blocks.

[0043] S1.2, then placed in a muffle furnace, heated to 825~860℃, kept warm for 2~3h for pre-sintering, and then ground using a conventional ball mill at 250~350rpm for 12~16h, with anhydrous ethanol as the ball milling medium, to form a powder with an average particle size of 1~2μm, and obtain micron sintered powder, i.e. micron Mg (1-x) Sr x Zr 0.2 Ti 0.8 O3 matrix structure piezoelectric ceramic material;

[0044] S2. Preparation of Nano-Na (1-y) Sr y Ce 0.15 Ti 0.85 O3-based piezoelectric ceramic materials

[0045] S2.1, first use SrCO3, Na2CO3, CeO2 and TiO2 as raw materials, according to the chemical formula Na (1-y) Sr y Ce 0.15 Ti 0.85O3 calculates and weighs the required raw materials, where y is the molar fraction of Sr, y is 0.6-0.65, and mixes the raw materials using a conventional ball mill at 250-350 rpm for 16-24 hours. The ball milling medium is anhydrous ethanol, and the raw materials are dried at 85-95°C and pressed into blocks;

[0046] S2.2, then placed in a muffle furnace, heated to 825-860°C, kept warm for 2-3 hours for pre-sintering, and then ground with a high-energy ball mill at 450-550 rpm for 1-3 hours, with anhydrous ethanol as the ball milling medium, to form a powder with an average particle size of 300-650 nm, to obtain a nano-calcined powder, i.e., nano-Na (1-y) Sr y Ce 0.15 Ti 0.85 O3 matrix structure piezoelectric ceramic material;

[0047] S3. Preparation of lead-free composite piezoelectric ceramic materials

[0048] S3.1. Mix the micron calcined powder and the nano calcined powder in a molar ratio of 0.65:0.35 using a conventional ball mill at 250-350 rpm for 8-12 hours, using anhydrous ethanol as the ball milling medium, and dry at 85-95°C to obtain a mixed calcined powder;

[0049] S3.2, adding 0.45wt% of polyvinyl alcohol to the mixed calcined powder, using a conventional ball mill at 100-150rpm for 6-8h, mixing evenly, and then pressing into shape, and then cold isostatic pressing at 180-200Mpa for 30-60s to obtain a ceramic body;

[0050] S3.3, placing the ceramic body in a muffle furnace, sintering at 1000-1080°C for 4-8h, and then cooling to room temperature in the furnace to obtain a piezoelectric ceramic;

[0051] S3.4. Polarization treatment: The piezoelectric ceramic is covered with a platinum electrode and polarized in silicone oil at 140-150°C and a polarization electric field of 6-8 kV / mm for 25-35 min to obtain a lead-free composite piezoelectric ceramic material.

[0052] Preparatory Example 1

[0053] Preparation of micronized Mg (1-x) Sr x Zr 0.2 Ti 0.8 O3 matrix structure piezoelectric ceramic material, through the following steps:

[0054] S1.1, first use SrCO3, MgO, ZrO2 and TiO2 as raw materials, according to the chemical formula Mg in Table 1 (1-x) Srx Zr 0.2 Ti 0.8 O3 calculates and weighs the required raw materials, where x is the molar fraction of Sr, and x is shown in Table 1. The raw materials are mixed at 300 rpm for 20 h using a conventional ball mill, and the ball milling medium is anhydrous ethanol, which is dried at 90 ° C and pressed into blocks;

[0055] S1.2, then placed in a muffle furnace, heated to 845 ° C, kept warm for 2.5 hours for pre-sintering, and then ground using a conventional ball mill at 300 rpm for 14 hours, with anhydrous ethanol as the ball milling medium, to form a powder with an average particle size as shown in Table 1, to obtain a micron sintered powder, i.e., micron Mg (1-x) Sr x Zr 0.2 Ti 0.8 O3-based piezoelectric ceramic material, denoted as Wn, n is a digital number such as 1, 2, 3..., the results are shown in Table 1.

[0056] Table 1

[0057]

[0058] Preparatory Example 2

[0059] Preparation of Nano-Na (1-y) Sr y Ce 0.15 Ti 0.85 O3 matrix structure piezoelectric ceramic material, through the following steps:

[0060] S2.1, first use SrCO3, Na2CO3, CeO2 and TiO2 as raw materials, according to the chemical formula Na (1-y) Sr y Ce 0.15 Ti 0.85 O3 calculates and weighs the required raw materials, where y is the molar fraction of Sr, and y is shown in Table 2. The raw materials are mixed at 300 rpm for 20 h using a conventional ball mill, and the ball milling medium is anhydrous ethanol, which is dried at 90 ° C and pressed into blocks;

[0061] S2.2, then placed in a muffle furnace, heated to 845 ° C, kept warm for 2.5 hours for pre-sintering, and then ground at 500 rpm for 1.5 hours using a high-energy ball mill, with anhydrous ethanol as the ball milling medium, to form a powder with an average particle size as shown in Table 2, to obtain a nano calcined powder, i.e., nano Na (1-y) Sr y Ce 0.15 Ti 0.85 O3-based piezoelectric ceramic material, denoted as Nn, where n is a digital number such as 1, 2, 3..., the results are shown in Table 2.

[0062] Table 2

[0063]

[0064] Examples and Comparative Examples

[0065] The lead-free composite piezoelectric ceramic material is prepared by the following steps:

[0066] S3.1. The micron calcined powder Wn shown in Table 1 and the nano calcined powder Nn shown in Table 2 are compounded according to the combination shown in Table 3 and the molar ratio shown in Table 3, and mixed by conventional ball milling at 300 rpm for 10 h, the ball milling medium is anhydrous ethanol, and dried at 90° C. to obtain a mixed calcined powder;

[0067] S3.2, adding 0.45wt% polyvinyl alcohol to the mixed calcined powder, mixing for 7h at 120rpm using a conventional ball mill, mixing evenly, pressing into shape, and cold isostatic pressing for 50s at 190Mpa to obtain a ceramic body;

[0068] S3.3, placing the ceramic body in a muffle furnace, sintering at 1050°C for 6 hours, and then cooling to room temperature in the furnace to obtain a piezoelectric ceramic;

[0069] S3.4. Polarization treatment: The piezoelectric ceramic is covered with a platinum electrode and polarized for 30 minutes in silicone oil at 140-150°C and a polarization electric field of 7 kV / mm to obtain a lead-free composite piezoelectric ceramic material, as shown in Table 3.

[0070] Table 3

[0071]

[0072] The lead-free composite piezoelectric ceramic materials prepared in the above-mentioned Examples 1 to 9 and Comparative Examples 1 to 14 were cut into rectangular ceramic samples with a size of 10 mm×2 mm×1 mm. The ceramic samples were tested to determine the piezoelectric constant d33 and the relative dielectric constant ε r , electromechanical coupling coefficient Kp, mechanical quality factor Qm and density ρ, the results are shown in Table 4. The larger the piezoelectric constant d33, the higher the piezoelectric performance, and the larger the mechanical quality factor Qm, the smaller the loss of the ceramic during resonant vibration.

[0073] Table 4

[0074]

[0075] It can be seen from Table 1 that compared with Comparative Examples 1 to 14, the piezoelectric constant d33 of the lead-free composite piezoelectric ceramic materials in Examples 1 to 9 is between 340 and 401 pC / N, and the relative dielectric constant εr The mechanical coupling coefficient Kp is between 35% and 44%, the mechanical quality factor Qm is between 167% and 178%, and the density ρ is between 7.64% and 7.69g / cm 3 , has high piezoelectric performance and small dielectric loss, and good density; and the piezoelectric constant d33 and relative dielectric coefficient ε of the lead-free composite piezoelectric ceramic material prepared by the present invention are r , electromechanical coupling coefficient Kp, mechanical quality factor Qm and density ρ change little and are relatively stable.

[0076] In addition, the relative dielectric constants ε of the lead-free composite piezoelectric ceramic material samples prepared in Example 1 and Comparative Example 1 are r The test was carried out with temperature changes, and the results are as follows Figure 1 The relative dielectric constant ε shown r Curve graph of changes with temperature. As can be seen from the figure, the Curie temperatures of the lead-free composite piezoelectric ceramic materials prepared in Example 1 and Comparative Example 1 are 779°C, 792°C, and 795°C, respectively, and the rate of change of the dielectric constant of the lead-free composite piezoelectric ceramic materials prepared in Example 1 and Comparative Example 1 with temperature is very small in the range of room temperature to 660°C, indicating that the dielectric properties are good within this temperature range and can be used at high temperatures.

[0077] In summary, the lead-free composite piezoelectric ceramic material prepared by the present invention effectively avoids the decrease of d33 while obtaining good Qm, has high piezoelectric performance and small dielectric loss, improves the room temperature volume resistivity and density of the lead-free composite piezoelectric ceramic material, makes the performance of the lead-free composite piezoelectric ceramic material more stable, and can be well applied to high temperature conditions.

[0078] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit and essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0079] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A lead-free composite piezoelectric ceramic material, characterized in that: By micron Mg (1-x) Sr x Zr 0.2 Ti 0.8 O3-based piezoelectric ceramic materials and nano-Na (1-y) Sr y Ce 0.15 Ti 0.85 The O3-based piezoelectric ceramic material is composited by adjusting the molar ratio of the two, wherein x and y are the molar fractions of Sr, x is 0.72-0.8, and y is 0.6-0.66; In lead-free composite piezoelectric ceramic materials, Mg (1-x) Sr x Zr 0.2 Ti 0.8 The particle size of O3-based piezoelectric ceramic materials is 1~2μm; Na (1-y) Sr y Ce 0.15 Ti 0.85 The particle size of O3 matrix piezoelectric ceramic material is 300~650nm; The Mg in the lead-free composite piezoelectric ceramic material (1-x) Sr x Zr 0.2 Ti 0.8 O3-based piezoelectric ceramic materials and Na (1-y) Sr y Ce 0.15 Ti 0.85 The molar ratio of the O3-based piezoelectric ceramic material is 0.65:0.

35.

2. A method for preparing the lead-free composite piezoelectric ceramic material according to any one of claims 1, characterized in that: Prepared by the following steps: (1) SrCO3, MgO, ZrO2 and TiO2 are first used as raw materials, mixed, briquetting, pre-sintered and ground to obtain a micron calcined powder with a particle size of 1-2 μm; (2) First, SrCO3, Na2CO3, CeO2 and TiO2 are used as raw materials, and the mixture is mixed, pressed, pre-sintered and ground to obtain a nano-calcined powder with a particle size of 300-650 nm; (3) drying the mixture of the micron calcined powder and the nano calcined powder, adding a binder to mix, and then pressing, cold isostatic pressing, and sintering to obtain a piezoelectric ceramic; (4) The piezoelectric ceramics are polarized to obtain a lead-free composite piezoelectric ceramic material.

3. The method for preparing a lead-free composite piezoelectric ceramic material according to claim 2, characterized in that: The specific preparation steps of the lead-free composite piezoelectric ceramic material are as follows: S1. Preparation of micronized Mg (1-x) Sr x Zr 0.2 Ti 0.8 O3-based piezoelectric ceramic materials S1.1, first use SrCO3, MgO, ZrO2 and TiO2 as raw materials, according to the chemical formula Mg (1-x) Sr x Zr 0.2 Ti 0.8 O3 calculates and weighs the required raw materials, where x is the molar fraction of Sr, and x is 0.72-0.

8. The raw materials are mixed using a conventional ball mill, dried, and pressed into blocks; S1.2, then place it in a muffle furnace, heat it to 825~860℃, keep it warm for 2~3h for pre-sintering, and then use a traditional ball mill to grind it to form a powder with an average particle size of 1~2μm, and obtain micron calcined powder, i.e. micron Mg (1-x) Sr x Zr 0.2 Ti 0.8 O3 matrix structure piezoelectric ceramic material; S2. Preparation of Nano-Na (1-y) Sr y Ce 0.15 Ti 0.85 O3-based piezoelectric ceramic materials S2.1, first use SrCO3, Na2CO3, CeO2 and TiO2 as raw materials, according to the chemical formula Na (1-y) Sr y Ce 0.15 Ti 0.85 O3 calculates and weighs the required raw materials, where y is the molar fraction of Sr, y is 0.6-0.65, mixes the raw materials using a conventional ball mill, dries and presses into blocks; S2.2, then placed in a muffle furnace, heated to 825~860℃, kept warm for 2~3h for pre-sintering, and then ground using a high-energy ball mill to form a powder with an average particle size of 300~650nm to obtain a nano calcined powder, i.e., nano Na (1-y) Sr y Ce 0.15 Ti 0.85 O3 matrix structure piezoelectric ceramic material; S3. Preparation of lead-free composite piezoelectric ceramic materials S3.1, mixing the micron calcined powder and the nano calcined powder according to a certain molar ratio using a conventional ball mill, and drying to obtain a mixed calcined powder; S3.2, adding a binder to the mixed calcined powder, mixing it evenly using a conventional ball mill, and then pressing it into shape, and then cold isostatic pressing to obtain a ceramic body; S3.3, placing the ceramic body in a muffle furnace for sintering, and then cooling to room temperature in the furnace to obtain a piezoelectric ceramic; S3.

4. Polarization treatment: The piezoelectric ceramic is covered with a platinum electrode and polarized in silicone oil to obtain a lead-free composite piezoelectric ceramic material.

4. The method for preparing a lead-free composite piezoelectric ceramic material according to claim 3, characterized in that: In steps S1.1, S1.2, S2.1, S3.1 and S3.2, the milling medium of conventional ball milling is anhydrous ethanol; in step S2.2, the milling medium of high-energy ball milling is anhydrous ethanol.

5. The method for preparing a lead-free composite piezoelectric ceramic material according to claim 3, characterized in that: In steps S1.1 and S2.1, the rotation speed of the traditional ball mill is 250~350rpm, and the time is 16~24h; in step S1.2, the rotation speed of the traditional ball mill is 250~350rpm, and the time is 12~16h; in step S2.2, the rotation speed of the high-energy ball mill is 450~550rpm, and the time is 1~3h; in step S3.1, the rotation speed of the traditional ball mill is 250~350rpm, and the time is 8~12h; in step S3.2, the rotation speed of the traditional ball mill is 100~150rpm, and the time is 6~8h.

6. The method for preparing a lead-free composite piezoelectric ceramic material according to claim 3, characterized in that: In step S3.2, the pressure of the cold isostatic pressing is 180-200 MPa, and the pressure is maintained for 30-60 seconds.

7. The method for preparing a lead-free composite piezoelectric ceramic material according to claim 3, characterized in that: In step S3.2, the binder is polyvinyl alcohol, and the amount of the binder added is 0.45wt% of the mixed calcined powder.

8. The method for preparing a lead-free composite piezoelectric ceramic material according to claim 3, characterized in that: In step S3.4, the polarization temperature is 140-150°C, the polarization electric field is 6-8 kV / mm, and the polarization time is 25-35 min.

Citation Information

Patent Citations

  • Method for producing nano-micrometre double-scale crystal grain composite PZT piezoelectric ceramic

    CN101172857A

  • Lead-free ceramic material with high energy storage and charge-discharge performance and preparation method thereof

    CN110759727A